Efficiency of the Activities of County Labor Offices in Reducing Unemployment in the Central Macroregion of Poland in 2021 - Kucharski, Adam; Lekka-Porębska, Ilona (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
The year 2021, from the point of view of the labor market and the economy in general, differs clearly from the last few years. The most important reason for this is the lifting of restrictions introduced due to the pandemic caused by the SARS‑COV–2 virus. One of the effects of restrictions was the deterioration of the situation on the labor market, which after all slowly began to recover. In that work, authors decided to present the situation in the labor market of the central macroregion in Poland in 2021 and to examine the effectiveness of actions taken to reduce unemployment by county labor offices in the aforementioned area. Efficiency study was carried out using the DEA model taking into account uncontrollable results. Next, authors assessed the significance and strength of the variables impact describing regional conditions on the performance indicator from the DEA model using the tobit model. The data were received from voivodship and county labor offices, the Central Statistical Office and the Ministry of Family and Social Policy. The study showed that in 2021 the situation on the labor market improved (compared to 2020). Unemployment started to fall in the central macroregion, although these changes are not uniform in all poviats. Only one‑fifth of poviat labor offices converted inputs into results in an optimal way. Among the other offices, there was often a very strong efficiency. The tobit model indicated which variables significantly affect the effectiveness of poviat labor offices. In author’s opinion, the inefficiency of employment offices is not only caused by solutions, that have been implemented. After the pandemic subsided, unfavorable phenomena were observed on the labor market, on which offices have little or no influence. These include a large increase in the share of the long‑term unemployed in the total number of unemployed and a large number of people who repeatedly register as unemployed. This group of the voluntarily unemployed is rarely interested in the activities of county labor offices addressed to them.